CLINICAL, LABORATORY, AND IMMUNOLOGICAL FEATURES OF PATIENTS WITH BRONCHOPULMONARY DISEASES - Kalandarova D.O (TADQIQOTLAR, 2026)
Introduction Respiratory system diseases continue to represent a major challenge in contemporary medicine due to their high prevalence and significant contribution to morbidity and mortality worldwide, including in Uzbekistan. Numerous reports indicate that respiratory diseases rank among the leading causes of illness, with incidence rates increasing approximately 2.5 times in recent years [1]. Pneumonia, in particular, remains one of the most life-threatening infectious diseases; in 2019 alone, it was responsible for nearly 2.5 million deaths globally, including about 672,000 pediatric cases [2]. Bronchopulmonary disorders—such as chronic bronchitis, chronic obstructive pulmonary disease (COPD), pneumonia, and related conditions—not only impair patients’ quality of life and work capacity but also substantially increase disability and mortality rates [3].Bronchopulmonary diseases are characterized by both local and systemic inflammatory responses. Alterations in immune system function play a pivotal role in disease development and progression. Previous investigations have demonstrated that patients with chronic bronchopulmonary pathology often exhibit reduced immunological reactivity, manifested by decreased T-lymphocyte counts, disrupted lymphocyte subpopulation balance, diminished natural killer (NK) cell activity, and abnormalities in immunoglobulin levels [4]. These findings suggest the presence of secondary immunodeficiency, particularly in patients with severe disease courses [5], which in turn predisposes them to recurrent infections and dysregulated inflammatory responses. Study objective: To evaluate clinical manifestations, laboratory parameters, and immunological alterations in patients with bronchopulmonary diseases according to disease severity, and to perform statistical analysis in order to formulate evidence-based conclusions and clinical recommendations.